PERBANDINGAN HUKUM TATA NEGARA MENGENAI FUNGSI PENGAWASAN PARLEMEN ANTARA INDONESIA DAN SWEDIA: Comparison of constitutional law regarding the parliamentary oversight function between Indonesia and Sweden - Ervo, Jhenlee; Primananda, Eko (Faculty of Law, Universitas Trisakti, 2024)
The oversight function is the assignment of people’s representative organizations so government strategies and projects can be executed to make social government assistance and assume a significant part in the organization of state administration.The primary issue is,How does Indonesia's parliamentary authority compare to Sweden's,and what are the similarities and differences between Indonesia's and Sweden's oversight functions?This study uses normative research methods regarding comparative law based on statutory regulations,using secondary data obtained from a literature review,which is then qualitatively analyzed before the deductive method is used to draw conclusions.The conclusion is that a separate law regulates the comparison of parliamentary authority between Indonesia and Sweden regarding the regulation of parliamentary authority.The similarities in how the oversight function is carried out are then connected to the fact that it is governed by the law itself;the existence of special parliamentary function rules;the ability of the Indonesia People’s Representative organisation (DPR) to file a motion of no confidence in the government; the oversight of the implementation of laws and utilize your right to voice your opinions.The differences include: Execution of the obligations and powers of the parliamentary oversight function,;The parliamentary oversight function is categorized as supervision outside the institution and;Execution of inquiry rights.